Kaolin Particle Film Protects Grapevine cv. Cabernet Sauvignon Against Downy Mildew by Forming Particle Film at the Leaf Surface, Directly Acting on Sporangia and Inducing the Defense of the Plant - Wang, Ying; Cao, Xiao; Han, Yulei; Han, Xing; Wang, Zhilei; Xue, Tingting; Ye, Qiuhong; Zhang, Liang; Duan, Xinyao; Wang, Hua; Li, Hua (Frontiers in Plant Science, 2022)
Downy mildew is a major threat to viticulture, leading to severe yield loss. The use of traditional copper-based fungicides is effective, but has adverse effects on the environment and human health, making it urgent to develop an environmentally friendly disease management program. Multi-functional kaolin particle film (KPF) is promising as an effective and safer treatment strategy, since this material lacks chemically active ingredients. In this study, ability of Kaolin particle film (KPF) pretreatment to protect grapevine leaves from Plasmopara viticola was tested and the mode of action of KPF was analyzed. KPF application reduced the disease severity and the development of intercellular hyphae. Additionally, there was reduced accumulation of H2O2 and malondialdehyde (MDA) with pretreatment. The observation of ultrastructure on the leaf surface showed KPF deposition and stomatal obstruction, indicating that KPF protected plants against disease by preventing the adhesion of pathogens to the leaf surface and blocking invasion through the stomata. KPF pretreatment also activated host defense responses, as evidenced by increased activities of anti-oxidative enzymes [superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT)] and defense-related enzymes [phenylalanine ammonia-lyase (PAL), chitinases, and β-1,3-glucanases], increased phytohormone signals [abscisic acid (ABA), salicylic acid (SA), and jasmonic acid (JA)] and the up-regulation of defense genes related to plant defense. Overall, these results demonstrate that KPF treatment counters grapevine downy mildew by protecting leaves and enhancing plant defense responses.